Hubungan Antara Persepsi Beban Kerja dan Burnout pada ASN Bankesbangpol Provinsi Jambi - Khesyfa Hanan Kinanti; Fadzlul Fadzlul; Beny Rahim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Burnout is a psychological issue often faced by Civil Servants (ASN) due to demanding job responsibilities, negatively impacting performance, motivation, job satisfaction, and productivity. Excessive workload is a primary factor contributing to burnout, making it essential to examine their relationship in the governmental context. This study investigates the perception of workload and the level of burnout among civil servants at the National Unity and Political Agency (Kesbangpol) of Jambi Province. Using a quantitative correlational approach, the study involved 65 civil servants selected through purposive sampling. Data were gathered through an online questionnaire consisting of a workload perception scale (30 items) and a burnout scale (22 items). The Pearson Product Moment correlation test with SPSS software was used for data analysis. Descriptive results showed that most respondents reported moderate to high levels for both variables. A correlation coefficient of r = 0.503 with a significance level of p = 0.001 (p < 0.05) indicates a significant positive relationship between workload perception and burnout. This suggests that higher perceived workload increases the likelihood of experiencing burnout. To reduce burnout and maintain optimal performance, balanced workload management, social support, and stress management strategies are essential for civil servants.